Predominance of Conceptual Content in Teaching and Learning Physical Chemistry I - Peraza, Edward (2026)
Introduction.This study is part of a broader research project. In the context of the contemporary challenges of higher education, this study critically examines natural science teacher education through the voices of students, revealing tensions among curricular models, teaching practices, and the predominance of conceptual content. Purpose. The study aimed to understand, interpret, and generate a body of knowledge about the teaching and learning of Physical Chemistry I as a social construction developed by students enrolled in the Chemistry teacher education program at Universidad Pedagógica Experimental Libertador – Instituto Pedagógico de Barquisimeto (UPEL-IPB), Venezuela. Methodology. The study was grounded in a social constructionist epistemology and an interpretivist theoretical framework, guided by qualitative research and a phenomenological–hermeneutic approach. Social actors were selected through a purposive theoretical sampling, and in-depth interviews were conducted to explore the participants’ perspectives. The information obtained was coded and processed by triangulating the data, the interpretation of participants’ accounts, and the contribution of scholars who have examined these issues. Results and discussion. After subcategorization and categorization, the following category emerged: Conceptual content as a factor that conditions the teaching and learning of Physical Chemistry I. This category comprised three subcategories: conceptual content breadth, conceptual content irrelevance, and content–objective duality. Conclusions. A reductionist view focused on the conceptual content of the Physical Chemistry I course was identified, limiting the comprehensive preparation of future chemistry teachers. These findings highlight the need to reconsider the pedagogical approach by integrating theory, practice, and critical reflection in higher education, so that conceptual content is aligned with the educational purposes of the course and contributes to students’ holistic development.